Opportunities and Challenges of Using ChatGPT for the Affective Development of Students - Nur Rachmah, Aulia; Maksum, Muh.Nur Rochim (Universitas Muhammadiyah Surakarta, 2024)
This study aims to determine the opportunities and challenges of ChatGPT in the world of education and to find out also the advantages and disadvantages of ChatGPT in the world of education, especially regarding the affective realm consisting of spiritual, moral and ethical values. This research is a research that uses a descriptive qualitative approach, which describes a phenomenon by collecting data, in this case the use and utilization of ChatGPT. In the use of ChatGPT quite affecting the affective of students, among them from the spiritual and moral side tend to be ignored. Honesty is overlooked when students use ChatGPT, they don't care about the spiritual consequences, all students need is good and satisfactory grades without caring about the highly immoral process. This phenomenon is bad news that is quite sad in the world of education. The strategy of instilling values by instilling spiritual and moral values for students is necessary in looking at ChatGPT. strategies to prevent the impact of ChatGPT's shortcomings. An educator must be firm in supervising his students, a firm policy needs to be emphasized on students as well. One way that can be done is that academics warn that the use of ChatGPT can be done as long as it is balanced with binding regulatory regulations.